[OA162] Impact of scanner type and acquisition parameters on the accuracy of displayed computed tomography dose index. (August 2018) - Vigna, Luca Leandro; Cannillo, Barbara; Matheoud, Roberta; Ostan, Antonella; Dionisi, Clizia; Fusco, Gregorio; Brambilla, Marco
Abstract : Purpose: According to the EU directive 2013/59, the equipment used for computed tomography (CT) shall be able to inform the practitioner of relevant parameters for assessing the patient dose. Among them, the radiation output is usually displayed in terms of computed tomography dose index – CTDI [mGy]. The aim of this study was to measure the accuracy of the displayed CTDI100 for different manufacturers or models of CT and to assess the impact of acquisition parameters on CTDI100 accuracy. Methods: 10 CT from 4 different manufacturers (16-slices n = 6, 32-slices n = 1, 64-slices n = 3) were included in the study. The accuracy of the displayed CTDI100 was checked with a dosimeter with traceable calibration. Reference values for the displayed CTDI100 were derived from the equipment's manual. The impact of the CT model (16, 64, 128 slices), phantom size (head or body), kVp (80, 100, 120, 140 kVp) and primary collimation (from 1.25 to 40 mm, grouped in four level ⩽ 3, from 3 to ⩽ 10, from 10 to ⩽ 20, > 20 mm) on the accuracy of the displayed CTDI100, was assessed by a four-way factorial ANOVA. CT model, phantom size, kVp and primary collimation, were considered as independent variables (factors) and CTDI accuracy as the dependent variable. Results: All the factors had a statistically significant impact on CTDI100 accuracy (p < 0, 05). In a head to head comparison, the lower accuracies were found on average for sixteen channels CT (10 ± 5%), for 80 KV (15 ± 11%) and for thick collimations (13 ± 7%), whilst no significant differences were found between head and body phantoms. Conclusions: For sixteen channels CT and acquisition protocols involving the use of head phantom with low KV and thick primary collimation, the inaccuracies of the displayed CTDI can be higher than 20%, which is the suspension level indicated in the EC RP N.162 Publication for the accuracy of indicated dose parameters. This suggests the need of individual calibration of CT X-ray tubes by the manufacters and the necessity of including this check in the quality control programs for CT.